Pick up and dispose of pollutants from water via temperature-responsive micellar copolymers on magnetite nanorobots - Vaghasiya, Jayraj V; Mayorga-Martinez, Carmen C; Matějková, Stanislava; Pumera, Martin (Nature communications, 2022)
Nano/micromotor technology is evolving as an effective method for water treatment applications in comparison to existing static mechanisms. The dynamic nature of the nano/micromotor particles enable faster mass transport and a uniform mixing ensuring an improved pollutant degradation and removal. Here we develop thermosensitive magnetic nanorobots (TM nanorobots) consisting of a pluronic tri-block copolymer (PTBC) that functions as hands for pollutant removal. These TM nanorobots are incorporated with iron oxide (Fe3O4) nanoparticles as an active material to enable magnetic propulsion. The pickup and disposal of toxic pollutants are monitored by intermicellar agglomeration and separation of PTBC at different temperatures. The as-prepared TM nanorobots show excellent arsenic and atrazine removal efficiency. Furthermore, the adsorbed toxic contaminants on the TM nanorobots can be disposed by a simple cooling process and exhibit good recovery retention after multiple reuse cycles. This combination of temperature sensitive aggregation/separation coupled with magnetic propulsion opens a plethora of opportunities in the applicability of nanorobots in water treatment and targeted pollutant removal approaches.
Keywords: polymery; Ferrosoferric Oxide; Micelles; Temperature; Polymers; čištění vody; Water Purification; látky znečišťující životní prostředí; teplota; Environmental Pollutants; oxid železnato-železitý; micely